Empathy VR and the BeAnotherLab collective. Issue 2 (1st December 2020) - Doyle, Denise
BeAnotherLab were recipients of the 2017 STARTS Prize1 Honorary Mention for their work Library of Ourselves, an interdisciplinary and distributed project to create transformative encounters between communities in conflict. Described by the collective as an open book of embodied narratives, the ongoing archive of the Library of Ourselves is composed of stories recorded from a first-person perspective of individuals, belonging to various communities. The art collective based in Barcelona was formed almost a decade ago and consists of nine members from wide-ranging backgrounds. In this article I will discuss their engagement with empathy VR. I will draw on my interviews with a number of members of the collective and my meetings with them in Barcelona. I also discuss the significance of their work as an art collective and the impact this has on their arts practice.